2015
DOI: 10.1111/jcmm.12631
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of miR‐9‐dependent regulation of Myocd in PASMCs phenotypic modulation and proliferation induced by hepatopulmonary syndrome rat serum

Abstract: Hepatopulmonary syndrome (HPS) is characterized by a triad of severe liver disease, intrapulmonary vascular dilation and hypoxaemia. Pulmonary vascular remodelling (PVR) is a key feature of HPS pathology. Our previous studies have established the role of the pulmonary artery smooth muscle cell (PASMC) phenotypic modulation and proliferation in HPS-associated PVR. Myocardin, a robust transcriptional coactivator of serum response factor, plays a critical role in the vascular smooth muscle cell phenotypic switch.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Except mir-148a-3p, we were able to retrieve experimentally validated mRNA targets using miRTarBase 22 . For collected experimentally validated targets, see references in 23 34 for targets of miR-9a-5p 35 39 ; for miR-141-3p 38 , 40 46 ; for miR-200a-3p 38 , 44 , 47 ; for miR-200c-3p 38 ; for miR-429. Overlapped targets were represented graphically as a Venn diagram.…”
Section: Resultsmentioning
confidence: 99%
“…Except mir-148a-3p, we were able to retrieve experimentally validated mRNA targets using miRTarBase 22 . For collected experimentally validated targets, see references in 23 34 for targets of miR-9a-5p 35 39 ; for miR-141-3p 38 , 40 46 ; for miR-200a-3p 38 , 44 , 47 ; for miR-200c-3p 38 ; for miR-429. Overlapped targets were represented graphically as a Venn diagram.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that miRNA association results in translational repression, frequently accompanied by a considerable degradation of mRNAs by a non-RNAi mechanism (Filipowicz et al, 2008). Previous studies and our initial research have demonstrated that several miRNAs have roles in regulating the pathology of HPS, including miR-206, miR-199a-5p and miR-9 (Chen et al, 2014; Gao et al, 2015; Xu et al, 2015). To date, these findings are related to miRNAs regulating PASMC phenotypic modulation and proliferation.…”
Section: Introductionmentioning
confidence: 84%
“…Using the online miRNA database, we found that MYOCD is a virtual target of miR-9, and MYOCD has been reported to be involved in the pathogenesis of IA by regulating the contractility of smooth muscle cells [14]. In the present study we explored the relationship between miR-9 and MYOCD, finding that downregulation of MYOCD caused by upregulation of miR-9 leads to the development of IA.…”
Section: Introductionmentioning
confidence: 82%